Quality Of Life of Multi Drug Resistant Tuberculosis Cases of Kashmir Valley - Umar Nazir, Kousar Sideeq, Taha Ayub (International Journal of Innovative Research in Medical Science, 2017)
Background: Tuberculosis is a chronic disease; with serious repercussions on not only physical health buton overall well-being of an individual. Methods: A total of 66 cases were interviewed (33 Multi drug resistant tuberculosis & 33 Pulmonary Tuberculosis) using WHO BREF QoL Scale. Results: Out of the 66 patients interviewed (n= 33 MDR and 33 PTB), 45% were males and 55% were females. Surprisingly, among MDR cases, 2/3rd of cases were females. About 44% of individuals were of economically productive group. Pulmonary Tuberculosis patients fared significantly better than MDR patients in Domain scores. The mean differences in scores for the cases (MDRTB and PTB) were highly significant for all the domains and the overall Quality of Life (QoL). Conclusion: Tuberculosis affects all the predicted domains of QOL i.e. physical, psychological, health perceptions and social role functioning of an individual. The stigma associated with tuberculosis - be it pulmonary or MDR tuberculosis, is one of the major factor affecting the domains of Quality of life. Much needs to be done to dispel the stigma associated with Tuberculosis.